Combined and intravenous administration of TXA reduces blood loss more than topical administration in primary total knee arthroplasty: A randomized clinical trial - Lostak, Jiri; Gallo, Jiri; Balaz, Lubos; Zapletalova, Jana (Biomedical papers, 2022)
Aim. To determine the most effective administration of tranexamic acid (TXA) in patients with primary total knee arthroplasty (TKA). Material and Method. We enrolled a total of 400 patients (154 men and 346 women) in this randomized trial (4 groups, each of 100 patients). The first group (IV1) had a single intravenous dose (15 mg TXA/kg) prior to skin incision. Group 2 (IV2) had TXA in 2 intravenous doses (15 mg TXA/kg): prior to skin incision and 6 hours after the first dose. Group 3 (TOP) had 2 g TXA in 50 mL of saline irrigated topically at the end of the surgery. The fourth group (COMB) combined IV1 and TOP regimens. We monitored the amount of total blood loss (TBL), haemoglobin drop, use of blood transfusions (BTs), and complications in each patient. Results. The amount of TBL was significantly lower in IV1, IV2 and COMB regimens compared to the TOP (P<0.0001). The lowest decrease in haemoglobin within 12 hours after surgery was observed in intravenous regimens (P=0.045). A significant difference in haemoglobin decrease on day 1 after the surgery was demonstrated in the COMB and intravenous regimens (P=0.011). Conclusion. In primary TKA, it is preferable to administer TXA intravenously in two doses or in a combined regimen. Simple topical administration of TXA was not as effective and is indicated only in cases where systemic administration of TXA is contraindicated. No substantial complications occurred in either group of patients.
Keywords: total knee arthroplasty; tranexamic acid; topical administration; intravenous administration; combined administration; randomized clinical trial